THE CONSTRUCTION DECISIONS IMPROVEMENT OF ENERGY EFFICIENT FLOORINGS - Serdjuk, Vasyl; Franishina, Svitlana (Сучасні технології, матеріали і конструкції в будівництві, 2018)
A comparative analysis of the main operational characteristics traditional types of flooring structures, which are the most widely used in modern construction was carried out. The most perspective methods of prefabricated monolithic flooring, considering modern tendencies of new technologies, materials, organizational solutions are defined. The market supply of modern technologies of prefabricated monolithic flooring which characterized by relatively lower indicators of the flooring weight, increased thermal and sound insulation properties are analyzed. The constructive solutions for the prefabricated monolithic flooring by using cellular concrete blocks were improved.